Consumer Behavior: Components of Purchase Intention Products E-Commerce Perspective Maqāṣid Al-Sharīʿah - Rohani, Rohani; Hadidu, Andi; HM, Manda (Universitas Alma Ata, 2023)
Technological developments have led to changes in consumer shopping behavior from offline to online, leading to the emergence of various online marketplace platforms. The research discusses the influence of electronic of mouth (e-Wom), consumer rating, and reputation on product purchase intention in Shopee e-commerce. The population is Shopee customers, determining the sample with nonprobability techniques - purposive sampling with a sample size of 115 respondents. Analysis and hypothesis using the Structural Equation Model - Partial Least Square (SEM-PLS) method. The findings show that e-Wom, consumer rating, and reputation directly positively and significantly affect product purchase intention. The mediation test results prove that consumer rating and reputation partially mediate the effect of e-Wom on product purchase intention.